FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi Kasus Pada Mahasiswa Sekolah Tinggi Ilmu Ekonomi Nasional Banjarmasin) - Diana Hayati; Penta Lestarini Budiati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The purpose of this study was to determine whether the independent variables consisting of Culture (X1), Social (X2), Personal (X3), Psychological (X4) simultaneously or partially affect the purchasing decision (Y) of Samsung smartphone consumers and find out the most dominant in influencing purchasing decisions. The research method used in this research is quantitative descriptive method. The study population was students of STIE National Banjarmasin as many as 1,124 people and a sample of research using Samsung smartphones was taken as many as 92 respondents. The results of this study found that the variables Culture (X1), Social (X2), Personal (X3), Psychological (X4) together (simultaneously) had an influence on the Purchase Decision (Y) of Samsung smartphones. Then from the four independent variables, only Psychological variables (X4) have a significant partial effect on Samsung smartphone Purchasing Decisions (Y), while Culture (X1), Social (X2), Personal (X3) have no significant partial effect on Purchase Decisions (Y) Samsung smartphone.